Aspectos regulatórios da bolsa de valores no Brasil - Silva, Anderson Rodrigues da (2018)
Over the past decades, technological advances have been so significant, that it was not possible to accurately measure such effects; however, it is possible to say that communities worldwide have been transformed. Such transformation brought an impact on stock exchanges around the world as well as at the development of the capital market. It can be said that all areas of social interaction have been reached, ranging from the way people relate to each other, to the way the investors trade their shares on the stock exchanges. The purpose of this article is to analyse the development of the Brazilian stock exchange, its main aspects and characteristics, the way in which its regulation is made, its self-regulation, the securities market and the essential role of the Brazilian Securities and Exchange Commission (CVM), in favor of the market and its investors, in view of its significant social impact